FILSAFAT TEKNOLOGI YUSUF AL-QARADAWI: RELEVANSINYA TERHADAP PENGEMBANGAN MEDIA PEMBELAJARAN PAI KONTEMPORER - Burhan, Mohammad Nurul; Fajarwati, Anita; Maimun; Aufa, Ari Abi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information and communication technology has significantly transformed education, including Islamic Religious Education (PAI). However, the adoption of technology in PAI often lacks a strong philosophical foundation, which may lead to the erosion of spiritual and ethical values. Yusuf Al-Qaradawi, a moderate contemporary scholar (wasathiyah), offers a philosophical perspective that balances technological advancement with spiritual integrity. This study aims to examine Al-Qaradawi’s philosophy of technology and its relevance as an axiological and epistemological foundation for developing contemporary PAI learning media. This research employs a qualitative library research method with a descriptive-analytical approach. Primary data are derived from Al-Qaradawi’s works, while data analysis uses content analysis to identify key principles of technology in Islamic thought. The findings reveal that Al-Qaradawi’s philosophy is rooted in the concept of tashkhir, where technology serves as a means to achieve maslahah and devotion to God. Its relevance to PAI learning media includes three aspects: integrative (combining faith and digital literacy), ethical (guided by moral awareness), and adaptive (utilizing modern technologies such as AI and VR within Islamic principles). Therefore, technology in PAI should function not only as a tool but also as a medium to strengthen religious understanding and values.